Safer Tractor Operations for Landscape Maintenance and Horticultural Industries - Carol J. Lehtola; Charles M. Brown (EDIS)
This publication is one in a series of UF/IFAS Extension circulars devoted to tractor safety for various audiences. This document is CIR 1252, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published April 2003.